Students' voices on justice and equity: An experience in secondary school - Sandoval Mena, Marta; Echeita Sarrionandia, Gerardo; Simón Rueda, Cecilia (Pulso. Revista de educación, 2016)
This paper presents the process and the results of an exploratory work carried out on a secondary school that puts in practice the strategy of giving voice to students in order to develop policies of greater equity in school centres. Students´ voices can be a valuable tool to introduce improvements in schools, as reported in this experience carried out with 35 students through a designed questionnaire.
Keywords: Students Voices; Inclusive Education; Students Participation in their Teaching